Model Value Chain untuk Social Entrepreneurship - hani - sirine; Elia Elia Ardyan; Barnabas Theodore Pistos Utomo Kaya (UII, 2019)
The purpose of this research is to explain the CSR activities conducted by Marimas Putera Kencana related to the development of social entrepreneurship, to describe the value chain model for corporate entrepreneurship, and the impact of social entrepreneurship development through CSR activity. An explorative study approach was undertaken in this study by conducting semi-structured interviews at the Marketing Division of Marimas Putera Kencana, the target group, and the shop owners involved in the CSR program. The results of this study show the stages of CSR activities of Marimas Putera Kencana which include planning, implementation, evaluation, and reporting and value chain model for social entrepreneurship to realize business goals without overriding social values. In addition, the impact of social entrepreneurship development through CSR activities is the enhancement of environmental capacity and capability, creating leadership in the development of corporate social entrepreneurship, creating environmental protection, organizational transformation for social improvement, refreshing and promoting CSR development, awakening a positive reputation, and organizational commitment to continuously behave ethically.